2018
DOI: 10.1007/s12035-018-0996-x
|View full text |Cite
|
Sign up to set email alerts
|

Filamentous Aggregation of Sequestosome-1/p62 in Brain Neurons and Neuroepithelial Cells upon Tyr-Cre-Mediated Deletion of the Autophagy Gene Atg7

Abstract: Defects in autophagy and the resulting deposition of protein aggregates have been implicated in aging and neurodegenerative diseases. While gene targeting in the mouse has facilitated the characterization of these processes in different types of neurons, potential roles of autophagy and accumulation of protein substrates in neuroepithelial cells have remained elusive. Here we report that Atg7f/f Tyr-Cre mice, in which autophagy-related 7 (Atg7) is conditionally deleted under the control of the tyrosinase promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…The principal dimension of the observed structures is consistent in width and length with previous measurements in vitro 8 . The structures are compatible with recently observed aggregates of p62 in brain neurons and neuroepithelial cells 20 . Due to the limited length and flexibility, p62 filaments pack loosely into a spheroid-shaped, meshwork-like superstructure.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The principal dimension of the observed structures is consistent in width and length with previous measurements in vitro 8 . The structures are compatible with recently observed aggregates of p62 in brain neurons and neuroepithelial cells 20 . Due to the limited length and flexibility, p62 filaments pack loosely into a spheroid-shaped, meshwork-like superstructure.…”
Section: Discussionsupporting
confidence: 91%
“…Due to p62's involvement in protein homeostasis, the impairment of autophagy or oxidative stress results in aggregation or upregulation of p62, including increased body formation 19,20 . Recently, we and others independently found that p62 reconstituted with other components of the autophagy pathway, such as ubiquitinated model cargo, and the selective autophagy receptor NBR1, spontaneously coalesces into p62 bodies in vitro 21 and shows the characteristics of liquid-liquid-phase separation in vivo 22 .…”
mentioning
confidence: 99%
“…p62 protein is located at the site of autophagosome formation and can bind to autophagosome localization protein LC3 and ubiquitin protein. Therefore, p62 is a recognition receptor for ubiquitin protein and organelle degradation [17,36]. The decrease of p62 level leads to neuropathological changes, including excessive accumulation of tau and Aβ proteins, and even neuronal apoptosis [56].…”
Section: Discussionmentioning
confidence: 99%
“…Expressions of LC3Ⅱ was significantly increased in a dose-dependent manner ( Fig. 3d), suggesting an increase in the number of autophagic vacuoles, which may be due to elevation of autophagosome formation or suppression of autophagy degradation.In addition to LC3, the level of p62, as an autophagy substrate whichcan be attached to LC3 and ubiquitinated substrates, and then integrated into autophagosomes and degraded in autophagolysosomes [17,35], are significantly up-regulated ( Fig. 3d-e).…”
Section: Gas Reduces Cocl 2 -Induced Autophagosome Accumulation In Htmentioning
confidence: 99%
See 1 more Smart Citation